PENGARUH MEDIA VIDEO SCRIBE BERBASIS DARING TERHADAP KETERAMPILANMENULIS KARANGAN NARASI DAN MINAT BELAJAR SISWA PADA SISWA KELAS V SD INPRES GUNUNG SARI BARU KECAMATAN RAPPOCINI KOTA MAKASSAR - Astuti, Asmina; Sulfasyah; Munirah (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2022)
The purpose of this study was to determine the effect of narrative writing skills and interest in learning using online-based video scribe media in the fifth grade of SD Inpres Gunung Sari Baru, Makassar City. The research used is a quasi-experimental quantitative research. The design used is the Non-Equivalent Control Group Design consisting of two groups that were not selected at random using simple random sampling technique. From the test results using the sample t test on the skills of writing narrative essays, the significance value of Levene's Test for Equality is 0.620 > 0.05 with a coefficient value of 0.05. This value indicates that the data in this study is homogeneous, the significant value (Sig2-tailed) is 0.03 <0.05. So, it can be concluded that there is a significant effect on the skills of writing narrative essays using video scribe media. From the results of testing interest in learning, the significance value of Levene's Test for Equality is 0.751 > 0.05. This value indicates that the data in this study is homogeneous, the significant value (Sig2-tailed) is 0.04 < 0.05. So, it can be concluded that there is a significant effect on interest in learning to write narrative essays using video scribe media. From the results of the MANOVA test, the value of sig 0.00 <0.05, which means that there is a simultaneous effect of using video scribe media on narrative essay writing skills and student learning interest.